Probační a mediační služba - Dostalík, Ivo (Univerzita Pardubice, 2006)
V této práci je pojednáno o vzniku probačních a mediačních aktivit ve světě, jejich historickým vývojem a zavedením Probační a mediační služby v České republice, podstata a význam Probační a mediační služby v trestním řízení, naplnění jejího poslání a problémy spojené s uplatňováním této služby v našem právním a sociálním systému.

This work is dissertated about the origination of the probation and mediation activities in the world, about their historical development and the implementationof the probation and mediation service in the Czech republic, principles and point of this service in the criminal procedure, completion of its main purpose and problems associated with the assertion of this service in Czech legal and social system.
Probation and mediation service
Keywords: Probation; mediation; laws; generally beneficial services; alternative penalty; probace; mediace; PMS; zákony; obecně prospěšné práce; alternativní trest